Influence of moisture absorption on creep of GRP composite pipes - R. M. Guedes (2007)
The aim of this work was to study the influence of moisture absorption on long-term creep behavior of composite pipes. These pipes are used in water transportation which has an effect on the mechanical properties and on the polymeric composite matrix. Glass-reinforced thermosetting plastics (GRP) pipes are typically tested under ring deflection and/or internal pressure conditions. In this study, experimental creep data obtained from standard test methods under ring deflection conditions were used. This loading configuration simulates in the laboratory the external loads induced in a subsoil installation. The creep tests were performed on unconditioned and preconditioned specimens. Long-term mechanical behavior prediction based on short-term test data is necessary for design. For this purpose dynamic mechanical thermal analysis (DMTA) tests were performed on specimens machined from GRP pipes. Ten specimens were tested as delivered. Another 10 specimens were conditioned in water at room temperature and another 10 were conditioned in water at 50 degrees C, until saturation. The time-temperature superposition principle (TTSP) and extrapolation using a power law relation were applied to DMTA data for long-term creep prediction. Both methods were found to be conservative, i.e. predict higher stiffness reduction than the creep tests. Although creep tests were quite dissimilar from the DMTA tests, extrapolation using a power law relation appeared to be accurate enough to be used as a predictive tool for project design. Finally, comparisons of the DMTA data for different environment conditioning enabled the assessment of the hygrothermal effects on modulus.